Inculturation, Anthropology, and the Empirical Dimension of Evangelization - Ballano, Vivencio (Religions, 2020)
Using anthropological and theological perspectives and secondary literature, this paper argues that the scientific study of culture by professional anthropologists and social scientists is an essential component in the Catholic Church’s mission of evangelization through inculturation. Inculturation, the process of inserting the Christian message in society, requires scientific discernment to know which cultural traits are compatible with or contrary to the Christian faith, requiring anthropological training and active collaboration between theologians and professional anthropologists. Evangelization has incarnational and empirical dimensions when inserting the Gospel in human cultures. A genuine evangelization of cultures must be firmly rooted in the empirical reality of local cultures. The philosophical and theological orientation of many inculturationists and missionaries may sufficiently address the metaphysical dimension of the Christian faith, but not its empirical aspect when preached and adapted to human behavior in society, which entails scientific ethnographic research and active dialogue among clerics, missionaries, and social scientists.